Resilience of an Integrated Crop–Livestock System to Climate Change: A Simulation Analysis of Cover Crop Grazing in Southern Brazil - Peterson, Caitlin A.; Bell, Lindsay W.; Carvalho, Paulo C. de F.; Gaudin, Amélie C. M. (Frontiers in Sustainable Food Systems, 2020)
Integrated crop-livestock systems are a form of sustainable intensification of agriculture that rely on synergistic relationships between plant and animal system elements to bolster critical agroecosystem processes, with potential impacts on resilience to weather anomalies. We simulated productivity dynamics in an integrated cover crop grazing agroecosystem typical of southern Brazil to gain a better understanding of the impacts of livestock integration on system performance, including future productivity and resilience under climate change. Long-term historical simulations in APSIM showed that the integrated system resulted in greater system-wide productivity than a specialized control system in 77% of simulated years. Although soybean yields were typically lower in the integrated system, the additional forage and livestock production increased total system outputs. Under simulated future climate conditions (RCP8.5 scenario from 2020-2060), integrated system productivity exceeded specialized system productivity in 95% of years despite declines in average soybean yield and aboveground cover crop biomass production. While the integrated system provided a productivity buffer against chronic climate stress, its resilience to annual weather anomalies depended on disturbance type and timing. This study demonstrates the utility of process-based models for exploring biophysical proxies for resilience, as well as the potential advantages of livestock integration into cropland as a sustainable intensification strategy.